MAMMALIAN SEX HORMONES AFFECT REGENERATION CAPACITY AND ENZYMES ACTIVITY OF TRITICALE (X TRITICOSECALE WITTMACK) IN VITRO CULTURE - P. Uysal; I. Bezirganoglu (Journal of Animal and Plant Sciences, 2017)
This study is the first report that determines the effects of 17β-estradiol, estrone, progesterone and androsterone among the mammalian sex hormones on in vitro regeneration of Triticale mature embryos. A range of parameters which were 0 (control), 10-4, 10-8 and 10-12 m mol L−1 doses of 4 different mammalian sex hormones were investigated. It was clear that mature embryo interacted with the mammalian sex hormones. In mammalian sex hormones hormone applications, estron group gave the best result in terms of explant percentage forming shoots, followed by of progesterone group. Moreover, effects of mammalian sex hormones on proline and activities of enzymes in vitro regenere plantlets were investigated. Proline and activities of enzyme significantly increased at all the concentrations tested compared to control group. The maximum regeneration and enzyme activities were observed at the 10-12 m mol L−1 concentrations for all of four hormones in vitro culture.
Keywords: Triticale; mammalian sex hormones; enzyme activity; in vitro culture